Spirituality Magnetism in the Recitation of the Book of Al-Hikam: Inner Peace and Provision for Life in the Study of Intuitive Regions - Indah Rahayu; M. Ahmad Jamaluddin Zamzami; M. Adib Nuruzzaman; Myra Mentari; Iksan Iksan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to explore the dynamics of the Monday night religious gathering that studies Al-Hikam by Ibn 'Atha'illah as-Sakandari through a phenomenological approach. The research focuses on three main aspects: (1) understanding Al-Hikam as a guide for life through the lens of intuitive spirituality, (2) the ritual structure of the gathering as a religious tradition, and (3) the spiritual magnetism that consistently draws participants. Data were collected through participatory observation, in-depth interviews, and field study at Pondok Pesantren Kebon Sari, Kediri. The findings reveal that the gathering serves not only as a space for textual learning but also as a powerful medium for inner transformation. The internalization of Sufi values such as trust in God, sincerity, and patience combined with the charisma of the spiritual teacher and the solemn atmosphere of the gathering creates a profound spiritual experience. This gathering significantly contributes to inner peace, the strengthening of faith, and harmonious social relations, offering a transformative and contextually relevant model of spiritual education amidst the existential crises of modern society.